ANALISIS PENDEKATAN INTERNAL DAN EKSTERNAL KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK BATIK DI KAMPOENG BATIK LAWEYAN SURAKARTA - Moechammad Nasir (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2015)
This research in first year aim to to analyse influence signifikan among cultural factor, social factor, personal factor, and psychological factor to buying decision of batik product at Kampoeng Batik Laweyan Surakarta. Research done at chosen region that is: at Kampoeng Batik Laweyan Surakarta. internal issue in this research is what there are influence which signifikan among cultural factor, social factor, personal factor, and psychological factor to buying decision of batik product at Kampoeng Batik Laweyan Surakarta. Independent variable of this research are culture factor (X1), social factor (X2), personality factor (X3), and psychological factor (X4). And for dependen variable that is buying decision of batik product at Kampoeng Batik Laweyan Surakarta (Y). This research use primary and secundary data. Primary data obtained from technique of survey field by spreading quetioner at consumer buying batik at Kampoeng Laweyan Surakarta, while data sekunder obtained from various source publicized. Result of research indicate that the 1) variable of culture factor have the influence which signifikan to buying decision of product , social factor variable have the influence which signifikan to buying decision of product, variable of personality factor have the influence which signifikan to buying decision the product, and psychological factor variable have the influence which signifikan to decision buy the product 2) result of analysis test the F of variable of culture factor, social factor, personality factor, and psychological factor together have the influence which signifikan to buying decision of product 3) result of calculation to assess the R2 obtained 78,4% variation changing to decision product explained by variation changing of culture factor, social factor, personality factor, and psychological factor. While the rest equal 21,6% explained by other factor which don’t observation.